2011
DOI: 10.1007/s10354-011-0881-y
|View full text |Cite
|
Sign up to set email alerts
|

Children's health and RF EMF exposure. Views from a risk assessment and risk communication perspective

Abstract: A review of the scientific literature published until August 2010, covering epidemiological studies on the effects of RF EMF exposure on the incidence of brain tumours and leukaemia in children as well as experimental studies on RF EMF effects on cognition and CNS in children, reveals no or only scant evidence for the assumption that RF EMF exposure poses a hazard to children. This result is at odds with public risk perceptions, i.e. prevailing concerns of (at least part of) the public about adverse health eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…However, exposure to electromagnetic fields may also affect other functions of the human organism, including oxidative processes, resulting in disturbances of prooxidant/antioxidant balance in cells (so-called oxidative stress). Oxidative stress occurs in a situation when an excessive amount of generated reactive oxygen species (ROS) cannot be neutralized by an inefficient antioxidant defense system, resulting in an inability to detoxify the reactive intermediate products, which causes in consequence oxidative lesions of cell constituents, especially cellular membranes [32][33]. It is assumed that electromagnetic fields may affect proxidant/antioxidant balance in cells directly by impacting ROS generation and the activity of antioxidant enzymes or by systemic effect.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…However, exposure to electromagnetic fields may also affect other functions of the human organism, including oxidative processes, resulting in disturbances of prooxidant/antioxidant balance in cells (so-called oxidative stress). Oxidative stress occurs in a situation when an excessive amount of generated reactive oxygen species (ROS) cannot be neutralized by an inefficient antioxidant defense system, resulting in an inability to detoxify the reactive intermediate products, which causes in consequence oxidative lesions of cell constituents, especially cellular membranes [32][33]. It is assumed that electromagnetic fields may affect proxidant/antioxidant balance in cells directly by impacting ROS generation and the activity of antioxidant enzymes or by systemic effect.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…However, evidence that children are indeed more vulnerable to this exposure remains scant [Otto and von M€ uhlendahl, 2007;Leung et al, 2011;BioInitiative, 2012], and some studies have shown that effects in children did not differ from those in healthy adults [van Rongen et al, 2009;Croft et al, 2010;Segalowitz et al, 2010;Feychting, 2011;Valentini et al, 2011;Loughran et al, 2013]. The direct impact of RF exposure on neurodevelopment remains unknown, and the mechanisms that may be involved are poorly understood [Regel and Achermann, 2011;Loughran et al, 2013]; nevertheless, its negative health effects cannot be ruled out [Wiedemann and Sch€ utz, 2011], and some scientific reports of adverse effects may indicate that a reduction in exposure is warranted as a preventive measure, especially for children [Hardell and Sage, 2008;Divan et al, 2010;Rosenberg, 2013;Redmayne, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of adolescent users is estimated to have further increased [4] and politicians, public health officials and the scientific community show an increasing interest in the relation between children and adolescents’ health and radiofrequency radiation (RFR) exposure [5]. …”
Section: Introductionmentioning
confidence: 99%
“…The same review however emphasizes that the available literature cannot rule out adverse health effects of RFR due to the impossibility to prove a non-effect and due to the remaining knowledge gaps [5]. Several of the Interphone studies have found increased risks of glioma especially on the ipsilateral side after 10 years of exposure [6-9], however the pooled analysis of Interphone studies [10] concluded that “no increase in risk of glioma or meningioma was observed with use of mobile phones.…”
Section: Introductionmentioning
confidence: 99%